Dynamics of equilibrium structural fluctuations of apomyoglobin measured by fluorescence correlation spectroscopy - Chen, Huimin (National Academy of Sciences, 2007)
The spectra of equilibrium chain conformation fluctuations of apomyoglobin (apoMb) as a function of folding, from the acid-denatured state at pH 2.6 through the stable molten globule state pH ≈ 4.1 to the folded state at pH 6.3, are reported, as measured by fluorescence correlation spectroscopy. The conformational fluctuations, which are detected by quenching of an N-terminal fluorescent label by contact with various amino acids, can be represented by superpositions of decaying exponentials with time scales ranging from ≈3 to ≈200 μs. Both the time scales and amplitudes of the fluctuations increase with the degree of acid denaturation, with principal shifts associated with the transition across the molten globule state. Measurements of the diffusion of apoMb confirm theoretical values showing a ≈40% increase in the hydrodynamic radius upon acid denaturation. This study uses the model protein apoMb to illustrate the complex scope of folding associated structural dynamics.